Residual stiffness and strength of shear connectors in steel-concrete composite beams after being subjected to a pull-out pre-damaging: An experimental investigation. (August 2017) - Heng, Piseth; Bud, Mihai; Somja, Hugues; Hjiaj, Mohammed; Battini, Jean-Marc
Abstract: Horizontal stability of the medium rise steel frame structures is usually ensured by vertical bracings and diaphragm action of composite floors. Load transfer within the composite floor system is made through shear connectors, e.g. headed studs. In an event of explosion, such connectors must reserve sufficient residual stiffness and strength in order to avoid a sudden or delayed collapse of the building. These remaining capacities have not been experimentally studied yet in the literature. This paper presents large scale horizontal push out tests to determine the residual stiffness of the shear connectors after being initially damaged by explosion. The initial damaging is reproduced by a pull-out test using a quasi-static loading. Two types of numerical simulation have also been developed using ABAQUS/CAE software to provide a better understanding of the experimental results.